Hãy nhập câu hỏi của bạn vào đây, nếu là tài khoản VIP, bạn sẽ được ưu tiên trả lời.
\(\dfrac{3}{x-5}=\dfrac{-4}{x+2}\)=>3.(x+2)=(x-5).(-4)
=> 3.2+3.x=x.(-4)-(-4).5
=>6+3.x=x.(-4)-(-20)
=>3.x-x.(-4)=20-6
=>3.x-x.(-4)=14
=>x.(3+4)=14(vì 3-(-4)=3+4)
=>x.7=14
=>x=14:7
=>x=2
\(\left(x-1\right)^4:3^2=3^6\)
\(\left(x-1\right)^4=3^6.3^2\)
\(\left(x-1\right)^4=3^8\)
\(\left(x-1\right)^4=3^{2.4}=\left(3^2\right)^4=9^4\)
\(\Rightarrow\orbr{\begin{cases}x-1=9\\x-1=-9\end{cases}\Rightarrow\orbr{\begin{cases}x=9+1=10\\x=-9+1=-8\end{cases}}}\)
Vậy: \(\orbr{\begin{cases}x=10\\x=-8\end{cases}}\)
( x - 1 )4 : 32 = 36
( x - 1 )4 = 36 . 32
( x - 1 )4 = 38
( x - 1 )4 = 6561
( x - 1 )4 = 94
x - 1 = 9
x = 10
- a, Do \(\left[3x-15\right]^7=0\)
=> \(3x-15=0\)
=> \(3x=0+15\)
=> \(3x=15\)
=> \(x=15:3\)
=> \(x=5\)
\(\left(3x-5\right)^7=0\)
\(\Rightarrow3x-5=0\)
\(\Rightarrow3x=5\)
\(\Rightarrow x=\frac{5}{3}\)
\(a,0.25x\) - \(\frac{2}{3}x\) =\(1\frac{1}{6}\)
\(\Rightarrow x\cdot\left(0.25-\frac{2}{3}\right)=1\frac{1}{6}\)
\(\Rightarrow x\cdot\frac{-5}{12}=\frac{7}{6}\)
\(\Rightarrow x=\frac{7}{6}:\frac{-5}{12}\)
\(\Rightarrow x=\frac{-14}{5}=-2.8\)
-4.(2x+9)-(-8x+3)-(x+13)=0
(-4.2x+-4.9)+8.x-3-x+13=0
-8x+-36+8x-3-x+13=0
(8x-8x)-x=0+36+3-13
0-x=26
=>x thuộc rỗng
-2.(x+6)+6.(x-10)=8
(-2.x+2.6)+(6.x-6.10)=8
(-2+6).x+12-60=8
4.x=8+60-12
4.x=56
x=56:4
x=14